(x+3)/3=(2x-1)/7

Simple and best practice solution for (x+3)/3=(2x-1)/7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+3)/3=(2x-1)/7 equation:



(x+3)/3=(2x-1)/7
We move all terms to the left:
(x+3)/3-((2x-1)/7)=0
We calculate fractions
x/()+(-((2x-1)*3)/()=0
We calculate terms in parentheses: +(-((2x-1)*3)/(), so:
-((2x-1)*3)/(
We multiply all the terms by the denominator
-((2x-1)*3)
We calculate terms in parentheses: -((2x-1)*3), so:
(2x-1)*3
We multiply parentheses
6x-3
Back to the equation:
-(6x-3)
We get rid of parentheses
-6x+3
Back to the equation:
+(-6x+3)
We get rid of parentheses
x/()-6x+3=0
We multiply all the terms by the denominator
x-6x*()+3*()=0
We add all the numbers together, and all the variables
x-6x*()=0

See similar equations:

| 17(3x-5)-(9x-1)=B(3x-6) | | 400≠20x+240=240 | | 2(x+3)=5x+29 | | 2(x-3)^2-4=14 | | 2x^2+1x+7=0 | | 10x–2=3x+23 | | 4x+1=2(2+3) | | 5x=90+200+10 | | x/4=3/28 | | 5(2x+5)+3=8x+38 | | 6+12=4x-8 | | 0.15=y+.45 | | 25=y/2-9 | | 2x+10=50+6x | | 18x^2=-10x | | x–2=2x–9 | | (y^2+6)(-2y^2+7)=0 | | 25=y^2-9 | | 4v+8=56 | | 2t+2=0 | | 7(4+x)=3x | | 5x–5=4x+1 | | 50x+28=48x+32 | | 4+6(x+1)=-4+4(x-5) | | 19.75-8.25=m | | $19.75-$8.25=m | | 7x+41=90 | | 19.75-8.25=r | | -8(1-3v)=37=+9v | | 5x+7+x+8=180 | | u=8–u | | 5x-100=500 |

Equations solver categories